PWE-055 Characterisation of serum proteins in biliary tract cancer, primary sclerosing cholangitis and immunoglobulin G4-associated cholangitis using 2-dimensional difference gel electrophoresis and tandem mass spectrometry. (23rd September 2015) - Sandanayake, N S; Sinclair, J; Andreola, F; Chapman, M H; Camuzeaux, S; Webster, G J; Norton, I D; Smith, R C; Timms, J F; Pereira, S P
Abstract : Introduction: Distinguishing biliary tract cancer (BTC: cholangiocarcinoma and gallbladder carcinoma) from benign biliary disease such as pre-malignant primary sclerosing cholangitis (PSC) or immunoglobulin G4-associated cholangitis (IAC) can be difficult. Serum markers such as CA19.9 and immunoglobulin G4 lack sensitivity and specificity. There is a need for better biomarkers to differentiate these clinically similar diseases. We aimed to perform serum immunoaffinity depletion, 2-dimensional difference gel electrophoresis (2-DIGE) and liquid chromatography tandem mass spectrometry to identify differential biomarkers in benign and malignant biliary disease and healthy volunteers. Methods: Blood was prospectively collected from 37 patients with BTC, 11 with PSC, 7 with IAC and 30 healthy volunteers. Serum was pooled into the four clinical groups and immunoaffinity depleted via fast protein liquid chromatography to remove highly abundant proteins. Following 2-DIGE using minimal labelling Cy-dyes, gels were scanned then analysed with DeCyder software. Protein spots with a >2-fold differential expression (p<0.01, Student t test) were picked, trypsin digested and subjected to nanoflow reversed-phase liquid chromatography coupled to electrospray ionisation tandem mass spectrometry for protein identification. Results: The median age of BTC, PSC, IAC and healthy groups were similar at 68 (range 27–93), 47 (range 22–76), 63 (range 43–71) and 64 (range 40–79) years, respectively. The median serum bilirubin in the BTC, PSC and IAC groups was 40 (range 8–616), 20 (range 7–457) and 12 (range 5–40) μmol/l, respectively. 30/37 BTC, 4/11 PSC and 1/4 IAC patients, had elevated (>37 IU/ml) CA 19.9 levels. 61 protein spots were picked, of which 34 were upregulated and 13 downregulated in BTC vs healthy, 32 upregulated and 9 downregulated in BTC vs PSC, and 7 upregulated and 12 downregulated in PSC vs IAC. Leucine-rich glycoprotein, apolipoprotein A-IV and E, MASP2, CLEC3B, RAD1 and vimentin were upregulated and Hsp90, C4BPA and SERPIND1 downregulated in BTC vs PSC. Carbonic anhydrase 1, lumican and twinfilin-2 were upregulated and IgG4 chain C region and MASP2 were downregulated in PSC vs IAC, respectively. Serum validation of putative markers is underway. Conclusion: Differentially expressed serum proteins in benign and malignant biliary disease were identified using this proteomic approach. These putative markers may be useful in monitoring patients with PSC who are at increased risk of BTC.